Harmonics minimization of a three phase cascaded H-Bridge multilevel inverter - Sabari, Afiqah (2016)
For more than two decades, multilevel inverter technology has drawn tremendous interest among researchers from industry and academia in recent years due to its superior performance. In this regards, the main objectives of this this thesis are to study, modeling, design and develop a prototype of a three-phase cascaded H-Bridge Multilevel inverter (CHB-MLI) based on Newton-Raphson technique that aims to analyze the performance of the inverter output for harmonic minimization. The source codes programming based on Newton-Raphson method was developed, and then stored into the Digital Signal Processing (DSP) TMS320F2812. The proposed controller based on Newton Raphson was applied to CHB-MLI. The optimization of this system had managed to minimize the harmonic contents of the inverter output. Besides, the experimental results of the developed prototype are discussed. In addition, the performance of the proposed system was compared between simulation and experimental results for both Optimization and Non-optimization techniques. The Optimization of this system had been capable in reducing the harmonic contents of the inverter output. Thus, optimization and Non-optimization of the CHB-MLI system had been successfully demonstrated in this study. Finally the development of a three phase CHB-MLI based on DSP, its controller and power electronic devices would be a challenging future research in minimize the content of harmonic of the inverter output.